IMPLEMENTASI NILAI TAUHID, AMANAH DAN TRANSPARANSI DALAM PRODUKSI BROWNIES KUKUS KEWIRAUSAHAAN - Davina Felarisha; Zaskia Syifa Aida; Dimas Putra Utomo; Aryo Putra Maliki; Dava Dwi Aditya Fikriansyah; Sugiharto (PT. Saha Kreasi Indonesia, 2025)
This research examines how to principles of monotheism, trustworthiness, and transparency are applied within the production activities of steamed brownies as an expression of Islamic value- oriented entrepreneurship. The study is grounded in the growing relevance of spiritual values and ethical conduct in business practices, especially in the micro, small, and medium enterprise sector, which continues to encounter issues related to consumer. A qualitative methodology was employed using a case study approach focused on a steamed brownie business unit. Data were obtained through direct observation of production activities, depth in interviews with relevant stakeholders, and the review of business documentation. The finding indicate that the value of tauhid is manifested in business practices that position production activities as an act of worship, reflected in the careful selection of halal raw materials and the commitment to honesty throughout the manufacturing process. The value of amanah is reflected in the consistency of product quality, timely production, and responsibility for consumer orders. Meanwhile, the value of transparency is realized through openness regarding ingredient composition, production processes, and pricing. The implementation of these three values has been proven to contribute directly to increased consumer trust and business sustainability. This study concludes that the integration of the values of tauhid, amanah, and transparency is an important foundation in building ethical entrepreneurship with strong competitiveness.